Identificação do repertório de leitura de alunos da 2ª série do ensino fundamental de uma escola pública através de um programa computadorizado - Nibu, Marina Yayoi (2006)
The knowledge of the initial repertoire of each pupil is an important condition for planning an efficient education (Skinner, 1972). This because, if the teacher does not know what each pupil knows, it can plan the daily work in classroom, or on this side or beyond, of the necessities of the pupils. The present study had as objective to identify to the repertoire of reading of 20 pupils of 2nd grades of Basic Education of a public school in São Paulo State. The proposal was made possible by means of a procedure computerized with the aid of Mestre® software (Goyos, 1994) that, in agreement with the knowledge developed in the stimulus equivalence area (Sidman, 1971; Sidman & Tailby, 1982; De Rose, 1993; Souza and De Rose, 1997), works the reading as net of relations between stimulus of different modalities (sounds, images, texts). For the identification of the reading repertoire, instrument was used that allowed to evaluate the different relations in reading, as much of composed words only for simple syllables how much of words that contained complex syllables. The activities proposals had allowed detecting the individual diversity of repertoire of the pupils and their difficulties. The data had shown that almost half of the participant pupils of this research presents reading with understanding, therefore dominate the relation between stimulus of different modalities, as much of composed words for simple syllables, how much of that they have complex syllables. Small part of the pupils presents reading with understanding only of composed words for simple syllables, not dominating the relations between the different modalities of stimulus in composed words for complex syllables. Still, almost half of the participants presents difficulties in the evaluated relations, as much with composed words for simple syllables, how much with words that contain complex syllables. The data had shown that the repertoire of the pupils is diversified and that the types of complexity present in words of the Portuguese language intervene with the performance of the pupils, aspects that bring implications for the work of the teacher in classroom. The results gotten in this study indicate that there is an urgent necessity in planning specific interventions in the reading education, mainly, for those pupils who had presented low performance, through a individualized programming that more efficient and more adjusted, what it can be carried through using to advantage the new technologies of the modern world